Analysis Ecological Literacy Skill through Implementation of Learning Instruction Based on Local Potential Pulau Kembang - Purwasih, Desy; Wilujeng, Insih (Asian Journal of Science Education, 2023)
Ecological literacy needs to be trained for students so that the formation of human characters who care about the environment can be formed. Therefore, this study aims to analyse the ability of ecological literacy by implementing learning instructions based on local potential in eco-system materials and their components. This research is quantitative descriptive research. The population in this research is the student in grade seventh, and the total number of samples in this research is 60 students from junior high school in Banjarmasin. Ecological literacy questions consist of ten multiple-choice questions. The level of ecological literacy students can be identified with quantitative data that have been obtained and then converted into qualitative data (interval data). Based on the result, the first and second indicators get the high categorize with an average of 60.68% and 66.67%. The third until five hands get the medium to categorize with each average is 43.44%; 46.67%, and 56.67%. The result of the ecological literacy test can be used to develop learning instruction that is integrated with local potential.